2018
DOI: 10.1016/j.jagp.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Walking While Talking and Risk of Incident Dementia

Abstract: Complex walking as assessed by the WWT task is a simple and pragmatic tool for assessing risk of developing dementia, especially VaD, in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Prior studies have found evidence that fast-pace and cognitive dual-task walking tasks can predict changes in cognitive function. A study of non-demented individuals compared multiple metrics obtained while dual-tasking and found that variability but not speed was associated with higher probability of converting to dementia over 2 years [7]. In a separate cohort, slower fast-pace gait speed was associated with increased risk of Alzheimer’s disease over 11 years of follow-up among initially cognitively normal older adults [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have found evidence that fast-pace and cognitive dual-task walking tasks can predict changes in cognitive function. A study of non-demented individuals compared multiple metrics obtained while dual-tasking and found that variability but not speed was associated with higher probability of converting to dementia over 2 years [7]. In a separate cohort, slower fast-pace gait speed was associated with increased risk of Alzheimer’s disease over 11 years of follow-up among initially cognitively normal older adults [25].…”
Section: Discussionmentioning
confidence: 99%
“…Dual-task walking requires a person to walk while completing a concurrent, typically cognitively challenging, task. Greater gait slowing during cognitive dual-task walking is associated with conversion from either cognitively healthy status [7] or mild cognitive impairment (MCI) [8] to dementia. However, cognitive dual-task walking may be difficult to standardize clinically due to differences in types of secondary cognitive tasks [9] and difficulty in accounting for task prioritization [10].…”
Section: Introductionmentioning
confidence: 99%
“…The PFC has also been implicated in performance of DT (Sala et al, 1995;Dux et al, 2006;Filmer et al, 2013), that are motor tasks performed simultaneously with a secondary, usually a cognitive task. DT increases the cognitive demand of walking and potentially results in a decrease in task performance in one or both tasks relative to when the tasks are performed separately as ST. DT performance assessment may help identify older adults at higher risk of incident cognitive decline (Ceïde et al, 2018;Rosso et al, 2019), disability, frailty and mortality (Verghese et al, 2012). One of the goals of the study of cognitive aging is to elucidate neural mechanisms that underlie the ability of the aging brain to cope with decline in cognitive functions and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Dual‐task costs (DTCs) are exceptionally high in older adults with mild cognitive impairment and dementia (Odden et al, ) but they also affect relatively healthy older adults. Among these older adults without dementia, the walking‐while‐talking test (walking while reciting alternate letters of the alphabet; WWT), a mobility stress test, is a reliable predictor of falls, frailty, disability, incident dementia, and mortality (Ayers, Tow, Holtzer, & Verghese, ; Ceïde, Ayers, Lipton, & Verghese, ; Verghese et al, ; Verghese, Holtzer, Lipton, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%